1988
DOI: 10.1093/carcin/9.7.1153
|View full text |Cite
|
Sign up to set email alerts
|

The mutagenicity and DNA base sequence changes induced by 1-nitroso- and 1-nitropyrene in the cl gene of lambda prophage

Abstract: The mutagenicity of 1-nitropyrene and its reduced metabolite 1-nitrosopyrene was determined in the lambda cI gene of an Escherichia coli uvr- lysogen. 1-Nitropyrene induced a mutation frequency of 3.8 x 10(-6), which was approximately 2-fold higher than the background mutation frequency, whereas an equimolar dose of 1-nitrosopyrene induced a much higher mutation frequency of 1.4 x 10(-4). Previous studies have established that both compounds form the same premutagenic lesion, viz. N-(deoxyguanosin-8-yl)-1-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In both mammalian cells and bacteria, the major DNA adduct formed by 1-NP is N-(deoxyguanosin-8-yl)-1-aminopyrene [22][23][24]. 1-NP is also activated to a mutagenic DNA-binding species in bacterial cells via nitroreduction [25,26] to form N-(deoxyguanosin-8-yl)-1-aminopyrene as the major carcinogen-DNA adduct [23,27,28]. This adduct has also been detected in vivo but appears to account for only 20-57% of the total DNA binding [24].…”
Section: Discussionmentioning
confidence: 99%
“…In both mammalian cells and bacteria, the major DNA adduct formed by 1-NP is N-(deoxyguanosin-8-yl)-1-aminopyrene [22][23][24]. 1-NP is also activated to a mutagenic DNA-binding species in bacterial cells via nitroreduction [25,26] to form N-(deoxyguanosin-8-yl)-1-aminopyrene as the major carcinogen-DNA adduct [23,27,28]. This adduct has also been detected in vivo but appears to account for only 20-57% of the total DNA binding [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, AF dG mainly causes base substitution mutations 33,34 and induces a mixture of B and S damaged DNA conformations, 35 whereas AAF dG mainly promotes frameshift mutations 36,37 and a small amount of substitution mutations 37 but induces a mixture of the B, W, and S DNA conformations. 20 Finally, 1AP dG predominantly induces frameshift mutagenesis in bacteria 38 and results in the S conformation of damaged DNA. 39 Despite previous efforts toward elucidating the relationship between adduct structure and mutagenicity for individual N-linked C 8 -dG lesions, 23,24,39−41 systematic attempts to understand the effects of the size and shape of the NCA moiety on the structural characteristics of damaged (adducted) DNA are scarce.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, AF dG mainly causes base substitution mutations , and induces a mixture of B and S damaged DNA conformations, whereas AAF dG mainly promotes frameshift mutations , and a small amount of substitution mutations but induces a mixture of the B, W, and S DNA conformations . Finally, 1AP dG predominantly induces frameshift mutagenesis in bacteria and results in the S conformation of damaged DNA …”
Section: Introductionmentioning
confidence: 99%
“…one-base deletions or additions (13). In a subsequent study in pBR322, -1 deletions and all the targeted base substitutions were observed, but +1 additions were not detected (14).…”
mentioning
confidence: 79%